Cimino appointed to Air Force Academy (Raton Range Raton, New Mexico, 1990)
Newspaper Article on Richard Cimino who has been appointed to the United States Air Force Academy by Rep. Bill Richardson along with Sonya Bridges of Springer, New Mexico and 47 other New Mexicans to the nation's 3 prominent service academies.
Master list item #: 1
File location is in the Raton File Cabinet
Keywords: Cimino, Richard; Bridges, Sonya; Richardson, Bill; United States Airforce Academy; U.S. Military Academy; Naval Academy; Local History; Biography; Life and Customs; Officer training program; Leadership; Athletic Achievements; Raton, New Mexico; Colorado Springs, Colorado; West Point, New York; Annapolis, Maryland